Throughput Time Reduction of Complex, High Volume, Spare Parts A Study within the Assembly Department of an Automotive Components Manufacturer - Sommeren, Iris van; Tempel, David (My University, 2018)
The need for shorter lead times has always been one of the many desires for organisations in the automotive industry. It allows for quick adaption, higher margins and less uncertainties, however can be difficult to accomplish due to the large product portfolio and high product complexity. Especially in the spare part segment, where demand fluctuates and serial production is prioritised, it is challenging to comprehend. This thesis aims to contribute towards an understanding of how organisations, and more specifically the case company voestalpine, can reduce its lead time of the spare parts production without damaging risk and planning control. An extensive review of literature has led to the identification of potential causes and its accompanying effects on long lead times. These causes include the utilisation rate, preparation time, production time, discrepancies and waiting time. To gain more insight in possible disturbers within the voestalpine, an interactive AIM workshop has been executed. The outcomes combined with the cause-effect relationship has been the foundation for the assessment of a current process analysis. From this research, a portion of the aforementioned causes were eliminated as major lead time disturbers, since degree of influence was insignificant. A future process analysis of the remaining disturbers resulted in a generic decision tree, which will guide the improvements of production steps of spare parts in the assembly department. Restructuring bill-of-materials and adapting planning behaviour and production strategies has been proven in this research to the reduction of lead times. An average lead time reduction of 20,5%, or translated to 38 days, will allow the case company to approach customer demands and increase production flexibility.
Keywords: Produktion; Transport; Grundläggande vetenskaper; Hållbar utveckling; Övrig industriell teknik och ekonomi; Production; Transport; Basic Sciences; Sustainable Development; Other industrial engineering and economics